Self‐healing and chemical resistance polyurethane elastomers based on 2‐ureido‐4[1H]pyrimidinone. Issue 39 (28th July 2022) - Fu, Wenyu; Mei, Huifeng; Zhang, Zhijia; Wang, Qiang; Li, Rui; Zhang, Songsong; Wang, Guojun; Wei, Hao; Zhang, Chenyuan; Lin, Cunguo; Wang, Lei
Abstract: Self‐healing polyurethane elastomers allow increasing the life cycle, adapting to the circular economy, thus reducing the generation of waste. In this work, ureido‐4[1 H ]‐pyrimidinone (UPy) compounds was used to construct on supramolecular polymer. The self‐healing polyurethane elastomers were successfully prepared by supramolecular polymer based on UPy via a simple blending way. The self‐healing performance of the polyurethane elastomers with UPy were investigated by the scratch test and the cut‐off test, respectively. The scratch of the self‐healing polyurethane elastomer (PU‐15UPy) was totally healed in 1 h at 35°C. The tensile strength and the elongation at break of PU‐15UPy were 0.81 MPa and 563.8%. After the cut‐off test, the healing efficiencies of tensile strength were 63.8% (0.51 MPa) and 85.2% (0.69 MPa) after healing for 10 h at 35 and 80°C, respectively. The healing efficiency of tensile strength reached the value of 90.1% (0.73 MPa) after healing for 24 h at 80°C. The chemical resistance of the self‐healing polyurethane elastomers was tested by immersion in water, NaCl solution (3%), HCl solution (5%), NaOH solution (5%), and diesel, respectively. The mass loss of self‐healing polyurethane elastomers were all less than 2% after immersed in these solutions for 1 month, indicating the excellent chemical resistance performance of PU‐15UPy. Abstract : Self‐healing and chemical resistance polyurethane elastomer based on 2‐ureido‐4[1 H ]‐pyrimidinone was prepared by the simple blending method. The healing efficiency of tensile strength reached the value of 90.1% (0.73 MPa) at 80°C after healing for 24 h.